The effectiveness of exploitable zoning in the Boa Viagem neighborhood, in Recife/PE - Prado, Amanda Rafaely Monte do; Pessoa Neto, Amaury Gouveia; Lima, Karina Paula Barbosa de Andrade; Silva, Simone Rosa da (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
This study aimed to analyze the effectiveness of exploitable zoning in the neighborhood of Boa Viagem, city of Recife/ PE. For this, the information present in the three editions of the Hydrogeological Study of the Metropolitan Region of Recife, known as HIDROREC I, II and III, was used as subsidy, as well as the database of groundwater allocation, provided by APAC. From the analyses performed, an improvement in the level of the Cabo aquifer was obtained in Zone A of Boa Viagem, which may be related to compliance with Resolution CRH no. 04/2003. It can also be concluded that this resolution was being complied with in zone B. Thus, the importance of the exploitable zoning map is highlighted as an important tool for promoting groundwater management and conservation.